2000
DOI: 10.1046/j.1360-0443.2000.95110711.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of alcohol problems among elderly patients in a university hospital

Abstract: There may be a substantial prevalence of alcohol problems in elderly hospital patients. Research is needed to examine how generalized this problem is.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…In general, however, the prevalence for elderly inpatients is higher than for elderly people in the community, with estimates of 14% for patients in emergency departments, 18% for medical inpatients, and 23-44% for psychiatric inpatients 11. Among elderly people, socio-demographic factors associated with alcohol use disorders include being male,12 13 socially isolated,14 single,14 15 and separated or divorced 16…”
Section: How Common Is the Problem?mentioning
confidence: 99%
“…In general, however, the prevalence for elderly inpatients is higher than for elderly people in the community, with estimates of 14% for patients in emergency departments, 18% for medical inpatients, and 23-44% for psychiatric inpatients 11. Among elderly people, socio-demographic factors associated with alcohol use disorders include being male,12 13 socially isolated,14 single,14 15 and separated or divorced 16…”
Section: How Common Is the Problem?mentioning
confidence: 99%
“…These rates have ranged from 9% to 21% in inpatient settings (Ganry et al, 2000;Curtis et al, 1989), with similar prevalence rates (10 -15%) among older adults admitted to the emergency department (ED; Adams et al, 1992;Tabisz et al, 1991). The differences in reported rates by various studies have been explained by differences in the definition of alcoholism, the diagnostic criteria used, and the characteristics of hospitals examined in terms of patient socioeconomic background and level of care provided (Baird, Burge, & Grant, 1989;Moore et al, 1989).…”
Section: Introductionmentioning
confidence: 87%
“…Some of these studies focused on older adults residing in community settings (Barnes, 1979;Smart & Liban, 1981), whereas others were more interested in older adult patients being treated in health care delivery settings (Curtis et al, 1989;Ganry et al, 2000;Smothers, Yahr, & Ruhl, 2004;Smothers, Yahr, & Sinclair, 2003;Tabisz et al, 1991). An aspect of this issue that is less studied is the use and intensity of services consumed by older adults with alcohol-related conditions, specifically in terms of medical services (Adams et al, 1993;Garnick et al, 1997;O'Farrell et al, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…Of the 132 patients in the study, the researchers classified 9% as having an alcohol dependency problem (Speckens, Heeren & Rooijmans, 1991). Ganry, Dubreuil, Joly and Queval (2000) assessed 370 patients 65 years or older for alcohol problems. Based on a structured personal interview that questioned drinking patterns, past and present, the researchers concluded that 9% of the patients could be considered as having a problem with alcohol.…”
Section: Alcohol A) Prevalencementioning
confidence: 99%